Use of “natural therapy” technology in the framework of social and psychological rehabilitation of the elderly - Mykhailo A. Anishchenko; Ellina G. Pozdniakova-Kyrbiatieva; Yurii Volodymyrovych Mosaiev; Oleksandr V. Krasnokutskyi; Volodymyr V. Glazunov (AIMS Bioengineering, 2022)
The article is devoted to the peculiarities of using “natural therapy” technology in the process of social and psychological rehabilitation of the elderly. The article analyzes the relevance of the problem of social isolation, maladaptation and loneliness of elderly people in different countries of the world, and in Ukraine in particular, leading to sustainable social and psychological dysfunctions and substantiates the need to overcome them. The author's methodology for evaluating the effectiveness of socio-psychological rehabilitation sessions with the elderly using the rehabilitation implements of natural therapy is proposed. The mechanisms and technologies of social and psychological rehabilitation of the elderly using the rehabilitation concept of natural therapy are proposed and have been tested. As part of the research, an experiment was conducted among 100 people, half of whom were engaged in an individual rehabilitation course using the technology of the ecological rehabilitation concept of natural therapy. The article describes the results of the proposed classes for the participants of the experimental group and presents proposals in the field of improving rehabilitation measures based on natural therapy in the framework of the social and psychological rehabilitation of the elderly.